2020
DOI: 10.1007/s11764-020-00853-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of immunotherapy for survivors of stage IV non-small cell lung cancer: patient perspectives on quality of life

Abstract: Purpose The aim of this study was to examine what personally mattered to 24 patients who received immuno-oncology (IO) therapy for stage IV non-small cell lung cancer (NSCLC), as well as their families and friends, to understand how they evaluated their cancer treatments and the determinants of the quality of life (QoL) of long-term survivors. Methods Ethnographic research was conducted with 24 patients who had responded to IO (pembrolizumab, nivolumab, atezolizumab, or durvalumab) for stage IV NSCLC, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(96 citation statements)
references
References 60 publications
4
55
0
Order By: Relevance
“…Recognition and prediction the lung cancer in the earliest stage can increase the survival rate of the patients. Lung cancer has no symptoms in the early stages [2], [3], so it needs more than traditional detection to detect it. Cancer can be defined as a disease of altered gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition and prediction the lung cancer in the earliest stage can increase the survival rate of the patients. Lung cancer has no symptoms in the early stages [2], [3], so it needs more than traditional detection to detect it. Cancer can be defined as a disease of altered gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, findings from international studies have also highlighted the lasting and profound existential-related, social-related, financialrelated, treatment-related and disease-related uncertainities, adverse effects on physical and emotional health and well-being, and a perceived need among some for enhanced informational support and guidance. 23 24 26 41 42 Shared decision-making, where clinicians support patients to share responsibility for decisions, based on the best available evidence and considering the strengths and risks of various treatment options, 43 positively affects patients' treatment experiences 44 and 45 QoL in cancer care. However, it has been noted that existing cancer decision-making pathways for some patients focus on clinical management of disease rather than patients' preferences and priorities for cancer treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…41 Patients receiving immunotherapy and their informal carers have also experienced uncertainty related to communication and treatment decisionmaking. 24 47 Indeed, patients reported feeling hampered by a lack of clear information, 23 and carers experienced unclear communication regarding immunotherapy treatment. 47 Findings from a recent study 48 indicated that most recommendations for ICI treatment were made by physicians, though patients generally preferred to have the final say regarding treatment commencement.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In a qualitative study by Park et al, the experience of immunotherapy was divided in two phases: (1) the “avalanche”, a period of intense frustration and disorientation in search of effective treatment following diagnosis in which the disease determines large parts of one’s life and (2) the “living longer” phase, a timeframe characterized by a steady treatment plan without progression or adverse events in which components of the old life can be regained. Overall, immunotherapy was described as a positive experience, but also means a living in “limbo” and “cycling” between the two phases [ 13 ]. Many patients express a strong need for adequate information throughout the entire course of the disease and therapy.…”
Section: Introductionmentioning
confidence: 99%